Predictors and Trajectories of Educational Functioning in College Students With and Without Attention-Deficit/Hyperactivity Disorder - DuPau1, George J. (J Postsecond Educ Disabil, 2018)
College students with attention-deficit/hyperactivity disorder (ADHD) are at greater risk than peers for im-paired educational functioning; however, little is known regarding their longitudinal academic outcomes. This study examined: (a) differences between ADHD and control participants in academic outcomes (i.e., semester GPA, credits attempted, credits earned) over the first two years of college, and (b) factors that predict second year outcomes. A sample of 456 students (50% with ADHD; 51.8% female; 71.7% Caucasian) from 10 universities completed two annual assessments. Compared to students without ADHD, students with ADHD experience more academic difficulties that persist over two years. Motivation to study reported in year one was a significant predictor of year two GPA, suggesting the importance of providing services as early as possible to support students before they struggle.